End User Information as the Source of Advertising Revenue a Case Study in Saudi Arabia - Abdulaziz Mansour, Ezzat (International Journal of Engineering and Technology, 2018)
The internet users have increased all over the world and the same trend is seen in Saudi Arabia. This has forced the marketers to take advantage of the online advertising. This study was conducted in Saudi Arabia to understand the opinion on the streaming of advertisements while using the public wifi system. The study was a quantitative study where a structured questionnaire was distrubuted among the wifi users in the Saudi Arabia. The data included responses from 313 usable responses across different regions in Saudi Arabia. The survey showed that the users agreed to have advertisement streaming if they were provided with free wifi. The findings of this will help the marketers as well as the online business managers to capitalise the advantage of the online advertising system.Â Â